The moderating role of gender in the influence of learning motivation and classroom environment on the innovative thinking of fine arts sthdents in Chinese universities - Ghazali, Norliza; Yao, Yuan; Sulong, Rose Manisah (Global Academic Excellence, 2024)
In the twenty-first century, the cultivation of innovative thinking has become the theme of higher education. Governments are also gradually paying attention to the cultivation of innovative thinking. This study explores the status of research on innovative thinking of art majors in universities and tries to explore the relationship between innovative thinking of art majors and learning motivation and classroom environment, and whether gender as a moderating variable has an impact on it. Through the survey and empirical analysis of many art majors, it was found that there are gender differences in the influence of learning motivation and classroom environment on innovative thinking. The results suggest that gender plays an important role in the development of innovative thinking among art major college students. This study provides in-depth thinking from a gender perspective for the education of art majors and makes certain suggestions for educational practice. This study is a purely quantitative study. The study will use questionnaire survey method to investigate the art majors' university students.